A Gauss-Kuzmin Theorem for Continued Fractions Associated with Nonpositive Integer Powers of an Integer m≥2 - Dan Lascu (The Scientific World Journal)
We consider a family {τm:m≥2} of interval maps which are generalizations of the Gauss transformation. For the continued fraction expansion arising from τm, we solve a Gauss-Kuzmin-type problem.